A Cross Sectional Study on Sleep Hygiene Among Morning Shift School Going Children - Dixit, Sanjay; Sirohi, Suraj; Sakalle, Salil; Rokade, Rahul; Sirohi, Sugandha (National Journal of Community Medicine, 2013)
Introduction: Sleep hygiene is defined as “The controlling of all behavioural and environmental factors that precede sleep and may interfere with sleep”. It is practicing of the guidelines to ensure more restful, effective sleep which can promote daytime alertness, memory, performance & growth of children. Subnormal sleep hygiene is a major problem with school children. Objective: The aim of the study was to assess the various aspects of sleep hygiene in morning shift school going children. Methods: This study was carried out among 300 morning shift school going children of 6 to 12 years in different geographical sites in Indore city. After obtaining informed written consent, a pretested semi-structured questionnaire was administered to mothers of these children. The instrument also included the respective scoring in Epworth Sleepiness Scale (ESS). The data were analysed using appropriate statistical tests. Results: Among the study population, maximum (44.33%) children were from > 10 to 12 year of age. It was observed that the group having ESS ≥ 10 comprised of 25.8% out of total children taking day time naps (χ2=22.10/p value=0.000), 42.86% of total children who skipped meals frequently at night (χ2=80.69/p value=0.000). Discussion: The present study tried to find out the pervasiveness of sub normal sleep hygiene, most striking fact found was that 90% children had less than 10 hrs of daily total sleep i.e. less than the recommended for this age group, 14% of children were having poor sleep hygiene, while 10.67% of children were having their ESS score between 7 to 9 (borderline). Conclusion: All affected children need intervention to conquer and to prevent future risk of becoming sleep deprived, their parents should also be given health education and should be counselled about the proper methods of promoting sleep hygiene.